Digital Payment Loyalty Across Generations: Evidence from QRIS Users - Anisya Rahmelia; Mimin Aminah; Megawati Simanjuntak (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2026)
The rapid expansion of digital payment systems has accelerated the transition toward a cashless ecosystem in Indonesia, particularly through the adoption of the Quick Response Code Indonesian Standard (QRIS). However, limited studies examine how digital payment loyalty is formed. This study analyzes the determinants of QRIS usage loyalty while providing insights into variations across user groups. Data were collected from 175 QRIS users in the Jabodetabek region using an online survey and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that perceived ease of use, loyalty programs, and cashless society orientation positively influence trust, which in turn enhances user satisfaction. Satisfaction is identified as the strongest predictor of QRIS usage loyalty. The findings indicate that variations in user responses are reflected in the strength of relationships rather than fundamental structural differences.